Vietnam : Strengthening the Social Safety Net to Address New Poverty and Vulnerability Challenges - World Bank (Washington, DC, 2013)
As it transitions to Middle-Income Country (MIC) status, Vietnam is considering whether its social protection system is adequate to meet rapidly changing needs associated with strong economic growth, integration of its economy in regional and global markets, industrialization, urbanization and other economic and societal shifts. Vietnam's social safety net - programs with the following objectives: 1) alleviation of chronic poverty; 2) help to the poor in coping with the worst forms of shocks and transient poverty; and 3) promotion of human development for long-term poverty alleviation. This note aims to assess the system of social safety net programs currently in place in Vietnam and to gauge how well it covers the poor and vulnerable populations. This note highlights two messages: first, it identifies gaps in the current poverty reduction and social protection system - programs that help address urban vulnerability and poverty and that help the poor and vulnerable manage shocks - which could be closed through strengthened and more effective household-targeted social safety net programs. Second, in examining the existing core social safety net programs the note finds that, while targeting is respectable, their primary weakness lies in limited coverage. Based on these findings, this note strengthens household-targeted social safety net interventions in Vietnam as a complement to geographically-targeted poverty reduction programs and social insurance.